Not Out of Hate : a Novel of Burma. - Lay, Ma Ma (Research in International Studies, Southeast Asia Ser., 2019)
Ma Ma Lay's 1955 novel of the marriage between a rural teenager to a powerful Anglophile twenty years her senior, set in prewar Burma, is an engaging drama, finely observed work of social realism, and stirring rejection of Western cultural dominance by Burma's foremost female author and one of its preeminent voices for change.